THE ROLE OF ADDITIONAL EDUCATION IN THE DEVELOPMENT OF STUDENTS' CREATIVE ABILITIES - Eshmirzaeva Muslima Faxriddin kizi (Scholar Express Journal, 2023)
This article provides information about the role of additional education in the development of students' creative abilities, the role of extracurricular studies in the lives of elementary school students, and their positive role in their worldview
Keywords: School; story; thinking